Pemanfaatan Kotoran Hewan Ruminansia (Peternakan Sapi) Sebagai Biogas (Studi Kasus Jalan G.Obos IV Kota Palangka Raya) - mohammad Bagus Pambudi (Media Ilmiah Teknik Lingkungan (MITL), 2022)
The solid waste of cow is a problem to enviroment if many biomass the waste can be treated biogas, so it needs to be used as a product, namely biogas. The research can use to know and result of biogas with experiment method. Data analysis using simple statistics. The results of study indicate that the solid waste produced by the Kambing Palace and Padepokan Cows Mbah Brewok on Jalan G.Obos IV Palangka Raya City cant use by the owner and local community. The results of gas pressure measurements for 21 days with two treatments. Treatment I with a formula of 10 kg of solid waste and 9 liters of water, and treatment II with a formula of 15 kg of solid waste and 4 liters of water. The results of biogas pressure measurement treatment I total of 0.728 Psi and treatment II total of 1,111 Psi (P1 <P2). While the average biogas in treatment I 0.034 Psi, treatment II 0.052 Psi (P2> P1). shows the result of reseach potential for the use of solid waste ruminant (cow) manure as material making of biogas.